Comprehensive visual electrophysiological measurements discover crucial changes caused by alcohol addiction in humans: Clinical values in early prevention of alcoholic vision decline - Xie, Xin; Feng, Kang; Wang, Juan; Zhang, Min; Hong, Jing; Zhang, Haolin (Frontiers in Neural Circuits, 2022)
Alcohol addiction often compromises vision by impairing the visual pathway, particularly the retina and optic nerve. Vision decline in alcoholics consists of a sequential transition from reversible functional deterioration of the visual pathway to irreversible clinical vision degeneration or vision loss. Thus, the control of alcoholic vision decline should focus on prevention before permanent damage occurs. Visual electrophysiology is a promising method for early detection of retinal dysfunction and optic neuropathy, including full-field electroretinography (ffERG) and pattern-reversal visual evoked potential (PR-VEP). So far, however, research studying the electrophysiological characteristics in the preclinical stage of vision decline caused by alcohol addiction is still lacking. Here we conducted a retrospective study with 11 alcoholics and 14 matched control individuals to address this need. We had performed comprehensive visual electrophysiological tests, including ffERG and PR-VEP. We next analyzed all electrophysiological parameters using multivariate statistical analyses and discovered some highly sensitive alterations to alcohol addiction. We found severely reduced amplitudes in scotopic ffERG oscillatory potentials (OPs) in alcohol addicts. These changes indicate the alcohol-induced disturbances of amacrine cells and retinal circulation. In subjects with alcohol addiction, the amplitudes of b-waves diminish significantly in scotopic but not photopic ffERG, implying the impaired function of the retinal rod system and the dysfunction of the inner retina. PR-VEPs elicited by checkerboard stimuli with large 1 degree (°) checks mainly reflect the state of the optic nerve and ganglion cells, and PR-VEPs provoked by small 0.25° checks mainly reflect the function of the macular. We performed both measurements and observed a robust amplitude reduction in all three peaks (N75–P100, P100–N135) and a significant peak time extension in P100. Our research provides an affordable and non-invasive tool to accurately evaluate visual pathway conditions in alcohol addicts and help clinicians take targeted treatment.